TINDAK TUTUR DIREKTIF DAN STRATEGI BERTUTUR GURU MATA PELAJARAN BAHASA INDONESIA DI KELAS VII SMP NEGERI 31 PADANG - Monica, Lidya; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This article was written to describe the directive speech actions and speech strategies of Indonesian language teachers in class VII SMP Negeri 31 Padang. This research is qualitative with descriptive method. The sample of this study was grade VII students of SMP Negeri 31 Padang. The data of this research is the form of directive speech acts, speaking strategies and the context of the speaking of Indonesian language teachers in SMP Negeri 31 Padang in the 2018/2019 school year. The source of the research data is the speech of one Indonesian language teacher who teaches in class VII SMP Negeri 31 Padang. This research was conducted at the first meeting of the odd semester, for two meetings in the ongoing learning process.Based on the results of research and conclusions, it is suggested that the following things are suggested. (1) Directive speech acts and speech strategies of Indonesian subject teachers need to be developed, (2) Teachers are expected to use varied and good speech strategies to get the desired learning outcomes, (3) Teachers are expected to be able to use various examples of directive speech acts and appropriate speech strategies so that the process of speaking strategies that vary and discussion activities in the classroom become fun, and (4) the teacher is expected to be able to attract the attention of students in order to obtain a good learning process. Kata kunci: Tindak Tutur, Tindak Tutur Direktif, Strategi Bertutur